How does Sec63 affect the conformation of Sec61 in yeast? - Bhadra, Pratiti; Yadhanapudi, Lalitha; Römisch, Karin; Helms, Volkhard (PLOS Computational Biology, 2021)
Author summary The ribosome particles of a cell constantly synthesize fresh proteins. Some of these will be either integrated into organellar membranes or will be secreted from the cell. To this aim, they need to enter a channel protein complex termed translocon in the membrane of the endoplasmatic reticulum. The translocon needs to determine based on certain sequence features whether the peptide should be translocated into the endoplasmatic reticulum lumen or whether opening of a lateral gate will enable that its transmembrane domains slide laterally into the membrane. Whereas it is known that some peptides cannot be translocated without the involvement of accessory membrane proteins such as the Sec63 protein, the mechanistic details how Sec63 affects the conformation and/or dynamics of the translocon are so far not known. Here, we used molecular simulations, molecular docking and co-precipitation experiments to characterize protein contact residues and conformational shifts in the channel pore. Our simulations reveal that the plug moiety adopts different conformations in the channel in the presence, respectively the absence of Sec63, and we describe the influence of Sec63 on the conformation of the lateral gate. This study contributes to our understanding of the functionality of translocon and accessory proteins, and may eventually aid in characterizing and overcoming the effects of mutations related to protein translocation defects.